PEMANFAATAN SOLAR CELL SEBAGAI SUMBER ENERGI ALTERNATIF UNTUK FASILITAS DI WILAYAH DTA AZ-ZAHRA - Moch Irwan Hermanto, Moch Irwan Hermanto; Abdussalam, Abdussalam; Jiehad Akbar Pria Utama, Jiehad Akbar Pria Utama; Budiman Fauzi, Budiman Fauzi; Ganis Sanhaji, Ganis Sanhaji (Media Nusantara, 2022)
DTA Az-Zahra is a madrasa in RW 07 Dusun Leuwiliang, which is used as a place to study religion and a gathering center for RW 07 residents, which has power problems, namely frequent blackouts. Because of this, DTA Az-Zahra needs continuous electricity, so a solar cell installation work program was made. The purpose of installing solar cells is to convert solar energy into electrical energy which will be used for lighting and alternative electricity at the site. The method used in the implementation of solar cell installation using observation and interview methods. The working concept of this system uses a Polycrystalline Solar Module (50Wp). To make changes to the Solar Power Generation system, this Polycrystalline Solar Module (50Wp) converts solar energy into DC current. The resulting DC electric current will flow through the SSC controller to be able to charge electricity at the Accu and to determine the power received by solar panels from sunlight as well as the on-off output generated by the panel.